Suzuki‐Miyaura cross–coupling reaction in water: facile synthesis of (hetero) aryl uracil bases using potassiumorganotrifluoroborates under microwave irradiation. Issue 15 (26th September 2016) - Savitha, Bhaskaran; Sajith, Ayyiliath M.; Reddy, Eeda Koti; Kumar, C. S. Ananda; Padusha, M. Syed Ali
Abstract: In this paper, we report the use of (hetero) aryl potassiumorganotrifluoroborate salts as versatile nucleophilic organoboron reagents in the Suzuki‐Miyaura cross‐coupling reaction of an electron rich 6‐chloro 3‐methyl uracil in water under microwave irradiation. A comparative study of the cross‐coupling reaction of this chloro uracil analogue with different nucleophilic organoboron source revealed the superior reactivity of (hetero) aryl potassiumorganotrifluoroborates in water under microwave irradiation. Diversely functionalised (hetero) aryl uracil bases, which are known possess a wide range of applications in chemical biology, were efficiently synthesized using this optimised protocol. Abstract : In this paper, we report the use of (hetero) aryl potassiumorganotrifluoroborate salts as versatile nucleophilic organoboron reagents in the Suzuki‐Miyaura cross‐coupling reaction of an electron rich 6‐chloro 3‐methyl uracil in water under microwave irradiation. A comparative study of the cross‐coupling reaction of this chloro uracil analogue with different nucleophilic organoboron source revealed the superior reactivity of (hetero) aryl potassiumorganotrifluoroborates in water under microwave irradiation. Diversely functionalised (hetero) aryl uracil bases, which are known possess a wide range of applications in chemical biology, were efficiently synthesized using this optimised protocol.